O impacto da colonialidade do poder, do saber sobre a proteção dos direitos humanos dos migrantes : uma análise à luz das categorias migratórias - Castro, Sara Andreia da Silva (2024)
Migratory labelling are the ways in which doctrine and international law classify people who are migrating. Examples of labelling are the terms refugee, economic migrant, undocumented migrant and environmentally displaced person. As a rule, labelling are based on the reason for migration. Against this backdrop, the general aim of this dissertation is, by taking up and re-reading the hegemonic narratives of modernity based on the contributions of decolonial thought and its concept of coloniality, to verify the degree to which this mode of operation established during the colonial period is applied to contemporary migratory processes, especially those that are classified as a problem by international law. On the other hand, the specific objective is to verify, based on migratory categories such as migrant, undocumented migrant, refugee, involuntarily displaced person, among others, the extent to which the categorisation of migrants has meant greater protection or exclusion of these people in international law. The relevance of the subject is justified by the intensification of migration and its interfaces with human rights, considering that a significant part of migration in the world is seen as a problem and results in acts of repression by states with systematic violations of the rights of people in the process of migrating around the globe. The dissertation was prepared according to the following methodology: descriptive, dialogical and hermeneutic method with a predominance of the deductive method. The results of the master's dissertation were as follows: categorisations mirror the processes of modern racialisation applied to migratory processes, being instruments for distinguishing people on the basis of their origin and race and used in migratory governance to distribute different degrees of protection to people in migratory processes in international law. The work is divided into two chapters and their respective sub-headings. The first chapter is entitled "The construction of the human right to migrate: historical and normative elements", with the subheadings "Migration as a species of human mobility and as a genus of various migratory categories", "The Nation-State Model, its constituent elements and its relationship with migration", "The formation of international migratory regulations" and "Contemporary Migratory Flows". The second chapter was divided into two sub-headings entitled "Modernity and Coloniality: Race, Eurocentrism and Hierarchisation" and "The relationship between modernity, coloniality and biopolitics: contributions to the analysis of contemporary migratory processes". The dissertation makes a scientific contribution to the influence of coloniality and modernity on the migratory labelling currently taking place in the international community.